KINERJA PT.PLN (PERSERO) WILAYAH RIAU DAN KEPULAUAN RIAU TAHUN 2012-2014 (STUDI KASUS:KRISIS LISTRIK DI KOTA PEKANBARU) - Yoki Alvetro; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In 2013 Pekanbaru as the Capital City of Riau Province has electricity crisis. It caused powering outages to be trought byar pet until twelve hours in a day. UU No. 30 of 2009 Pasal 29 explained costumer deserve a good service and get good quality electric power continuously. PT.PLN (Persero) Wilayah Riau dan Kepulauan Riau that given a responsibility in provide electric power in Pekanbaru city said that condition is caused dry season and destruction one of power plants in Ombilin which become one of power plants in interconection system Riau province. The crises that happen for long time make all of society asking about PT.PLN (Persero) Wilayah Riau dan Kepulauan Riau performance in providing electric power in Riau province.The methode of this research is qualitative method that is not using numbers data but explanation that describe a situation, process, and particular condition. The techniques of data collection use documentation and interview technique.The result of the research describe the performance of PT.PLN (Persero) Wilayah Riau dan Kepulauan Riau is not good caused on of indicator performances is outcomes. This case is proved by many power plants has not finished on time and PT.PLN (Persero) Wilayah Riau dan Kepulauan Riau unfocuse to solve this crises cause fear of management to take decision while crises happen.Keyword : Electricity crisis,PT.PLN Wilayah Riau dan Kepulauan Riau, performance